Probabilistic finite element stiffness of a laterally loaded monopile based on an improved asymptotic sampling method - Vahdatirad, Mohammad Javad; Bayat, Mehdi; Andersen, Lars Vabbersgaard; Ibsen, Lars Bo (Journal of Civil Engineering and Management, 2015)
The mechanical responses of an offshore monopile foundation mounted in over-consolidated clay are calculated by employing a stochastic approach where a nonlinear p–y curve is incorporated with a finite element scheme. The random field theory is applied to represent a spatial variation for undrained shear strength of clay. Normal and Sobol sampling are employed to provide the asymptotic sampling method to generate the probability distribution of the foundation stiffnesses. Monte Carlo simulation is used as a benchmark. Asymptotic sampling accompanied with Sobol quasi random sampling demonstrates an efficient method for estimating the probability distribution of stiffnesses for the offshore monopile foundation.